Comercialização como estratégia de reprodução camponesa no Alto Sertão sergipano - Barreto, Ivan Siqueira (2014)
In Brazil, the contemporary peasant stemmed from a chapter of resistance to conservative proposals, passing through the slavery period, through the frustrating Law of Lands (1850), through the Getúlio Vargas´ developmental government, until the current engagement in the period of agribusiness predation of human and natural resources. This research had the backcountry peasants as subjects in focus to understand one of their reproduction strategies in their |territory|, which is the commercialization. The settlements of Curralinho with 30 families, Dom José Brandão with 41 families and Flor da Serra with 41 families were examined. All of them located on the territory of Sergipe´s high-hinterland, in the county of Poço Redondo. The study´s range proved to be pertinent by understanding that the local problems correspond and reproduce a global and structural field dynamics in the Sergipe´s hinterland. The peasant, person who has not had as historical heritage, an active participation in markets, has accumulated through time certain challenges for his/her insertion. Therefore, the study´s objective is to analyze how the peasant commercialization contributes to the social reproduction of the settled peasants in the county of Poço Redondo. As well, it is also the study´s objective to analyze how the territory is defined and relates to other sectors in society, developing itself through the commercialization that, concretely, we divide into direct sales, indirect sales, and with the institutional markets, by means of state´s public policies. For that, two methodological steps with different amplitudes were used: the first one was a more general look into the participative methodologies, reunions, group dynamics and participative diagnosis; the second one was developed in thirty selected questionnaires.